1992
DOI: 10.1007/bf00015110
|View full text |Cite
|
Sign up to set email alerts
|

Cyst hatching in Anostraca accelerated by retinoic acid, amplified by Calcium Ionophore A23187, and inhibited by Calcium-channel blockers

Abstract: Cyst hatching, under standardized conditions, of the Anostracan species Thamnocephalusplatyurus and Streptocephalus dichotomus was significantly accelerated but not increased by applying the morphogen retinoic acid (RA). Cyst hatching was enhanced but not accelerated by artificially increasing the inflow of c a 2 + to the embryonic cells, using Calcium Ionophore A 23 187. Cyst hatching was accelerated and amplified, to a level in excess of the summed effects of each treatment, by a combined application of RA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Horne (1966) found that the eggs of Artemia were resistant to avian digestive enzymes but found no difference in hatching fractions across treatments. Dumont et al (1992) increased hatching fractions (referred to as accelerated hatching) in anostracan eggs (Thamnocephalus platyurus Packard, 1877 and Streptocephalus dichotomus Baird, 1860) treated with retinoic acid and calcium ionophores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horne (1966) found that the eggs of Artemia were resistant to avian digestive enzymes but found no difference in hatching fractions across treatments. Dumont et al (1992) increased hatching fractions (referred to as accelerated hatching) in anostracan eggs (Thamnocephalus platyurus Packard, 1877 and Streptocephalus dichotomus Baird, 1860) treated with retinoic acid and calcium ionophores.…”
Section: Discussionmentioning
confidence: 99%
“…Dispersal studies using gene flow, point to dispersal being a rare or infrequent event due to strong patterns of genetic differentiation and founder effects among localised populations of passively dispersing seasonally astatic wetland organisms (Belk and Cole, 1975;Dumont et al, 1991;Fugate, 1992;Lynch and Spitze, 1994;De Meester et al, 2002;Bohonak and Jenkins, 2003). However, numerous studies demonstrate that passive dispersal occurs (Proctor, 1964;Horne, 1966;Moore and Faust, 1972; Rid- * E-mail: Branchiopod@gmail.com doch et al, 1994;Bohonak, 1999;Brendonck and Riddoch, 1999;Brendonck et al, 2000;Beladjal et al, 2007;Hulsmans et al, 2007;Sanchez et al, 2007;Vanschoenwinkel et al, 2008aVanschoenwinkel et al, , b, c, 2009Vanschoenwinkel et al, , 2011Beladjal and Mertens, 2009;Brochet et al, 2010;Waterkeyn et al, 2010;Schwentner et al, 2012) via mammals, birds, fish, amphibians, crayfish, insects, and wind.…”
Section: Introductionmentioning
confidence: 99%
“…Similar information was found by Santangelo et al (2010), showing that effects of vertebrate kairomones may not always infl uence the hatching rate and the time to hatching of ephippia in tropical aquatic ecosystems. Thus, the factors that induce the beginning and termination of the diapause can be more intimately related to the local environmental characteristics to which the organism is subjected, such as seasonality (Brandão et al 2014, Cáceres andTessier 2003), endogenous aspects of the eggs, such as egg age or maternal effects (Zadereev 2003) and calcium availability (Dumont et al 1992). Moreover, the eggs belonged to two different species, which could also infl uence the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Rozema et al 25 have shown high levels of aa-tRNA synthetases in diapausing compared to asexual eggs in Brachionus Ion transmembrane transport (16/147) Free ions in the cytosol restart the cell machinery by reactivating cellular enzymes 56 . Dumont et al 57 showed that cyst hatching in some anostraceans increased after the addition of mobile ion carriers. There is also evidence that increased pH induces diapause termination in Artemia salina 26 .…”
Section: Resultsmentioning
confidence: 99%